EMPLOYEE COMPETENCE AND MANAGEMENT OF GOVERNMENT TAX REVENUES RECEIVABLE: DOES KNOWLEDGE MANAGEMENT MATTER? - Ria Dewi Ambarwati; Amrie Firmansyah; Wing Hartopo; Iis Iswandy (JRAK, 2023)
This study examines employee competence's effect on the management of tax revenue receivables in the context of imports, with knowledge management as a moderating variable. The data used in this study was derived from a questionnaire survey distributed from March to July 2022 to the respondents, who were officials in the treasury unit that manages tax receivables and officials in the unit that handles financial statements in the Directorate General of Customs and Excise. This study concludes that employee competence and knowledge management positively affect the management of tax revenue receivables in the context of imports. However, knowledge management cannot strengthen employee competence's positive influence on tax revenue receivables in the context of imports.